Kajian Optimasi Pengoperasian Waduk Malahayu Kecamantan Banjarharjo, Kabupaten Brebes - Bambang Laras Media; Abdul Latif N; Wahudin Diantoro; Abdul Khamid (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Malahayu Reservoir is located in Malahayu Village, Banjarharjo District, Brebes Regency. Malahayu Reservoir was built in 1935. Malahayu Reservoir is planned to have a water storage capacity of 69 million m³ with a water surface area of 9.25 km². The main purpose of the construction of this reservoir is to supply irrigation water with a total area of 12,674 Ha, consisting of DI Kabuyutan of 4,166 Ha, DI Jengkelok of 6,173 Ha, and DI Babakan of 2,335 Ha. However, the water supply in Malahayu Reservoir continues to decrease, allegedly due to the high amount of sediment. The current problem is the occurrence of sediment in the Malahayu Reservoir. The pattern of operation using this reservoir needs to be studied because it is considered less optimal and because there needs to be a review of the use of reservoir water using newer data. That way, an operating pattern is needed to determine the reliability of reservoirs in their use as irrigation water providers. This study began by analyzing the secondary data obtained. Data is processed to obtain the amount of reservoir discharge and water needs for irrigation water. And the study ended with a simulation of the reservoir operation pattern. From the results of this study, it is expected to help provide solutions for the operation pattern of Malahayu Reservoir as an optimal reservoir. To improve the performance of the Malahayu Reservoir, supporting data such as reservoir operational systems and performance, hydrological data, reservoir operating procedures and patterns, and irrigation data are needed. The results of the analysis showed that the operation of the Malahayu Reservoir was less than optimal. Simulation of reservoir operation shows that the volume of water in Malahayu Reservoir is below the Minimum Operating Level (MOL), which is the minimum volume of water that should be in the reservoir. According to the records of the Cimanuk-Cisanggarung River Basin Center (BBWS), the condition of water supply in the Malahayu Reservoir continues to decline since this reservoir was built during the Dutch colonial rule until now.